The Essential Role of Human Resources Management in Healthcare and Its Impact On Facilitating Optimal Healthcare Services - Kemal M. Surji; Shirzad M. Sourchi (QALAAI ZANIST JOURNAL, 2020)
The role of Human resource management (HRM) in the healthcare sector is vital to facilitate optimum healthcare services by improving workforce performance and patient satisfaction. A solid understanding of the role of human resource management and related functions is required to safeguard the delivery of quality service and the success of the healthcare program. The study aims to explore the role and responsibilities of human resource management and its impact on the employee performance and value of healthcare services. The descriptive and investigative methodology was applied to analyze and review the previously published academic literature to obtain the influence of human resource management on the healthcare sector. The study illustrates that HRM functions in healthcare have a robust effect on facilitating optimal healthcare services and workforce performance, leading to heightening organizational performance. The study recommends that it is imperative to implement effective human resource management plans to achieve higher performance in providing superior healthcare amenities and further enhancement of healthcare organization.